Prestimulus oscillatory brain activity interacts with evoked recurrent processing to facilitate conscious visual perception. - Krasich, K; Simmons, C; O'Neill, K; Giattino, CM; De Brigard, F; Sinnott-Armstrong, W; Mudrik, L; Woldorff, MG (Springer Nature, 2022)
We investigated whether prestimulus alpha-band oscillatory activity and stimulus-elicited recurrent processing interact to facilitate conscious visual perception. Participants tried to perceive a visual stimulus that was perceptually masked through object substitution masking (OSM). We showed that attenuated prestimulus alpha power was associated with greater negative-polarity stimulus-evoked ERP activity that resembled the visual awareness negativity (VAN), previously argued to reflect recurrent processing related to conscious perception. This effect, however, was not associated with better perception. Instead, when prestimulus alpha power was elevated, a preferred prestimulus alpha phase was associated with a greater VAN-like negativity, which was then associated with better cue perception. Cue perception was worse when prestimulus alpha power was elevated but the stimulus occurred at a nonoptimal prestimulus alpha phase and the VAN-like negativity was low. Our findings suggest that prestimulus alpha activity at a specific phase enables temporally selective recurrent processing that facilitates conscious perception in OSM.